Integrated analysis of serum metabolomics and fecal microbiome in infants with necrotizing enterocolitis - Lin, Zhi-ying; He, Shan-shan; Mo, Zi-tong; Liao, Xiao-tian; Feng, Zhou-shan; Kong, Juan; Zhu, Lu; Li, Ying; Tan, Hui-yuan; Su, Zhi-wen; Jia, Chun-hong; Wu, Fan (Frontiers in Microbiology, 2025)
BackgroundNecrotizing enterocolitis (NEC), a lethal gastrointestinal disorder in preterm infants, remains poorly understood in its pathology, and early diagnosis are critically limited. Multi-omics approaches present unprecedented opportunities to elucidate NEC pathogenesis and identify clinically translatable biomarkers.MethodsInfants with Bell stage II-III NEC and gestational age-matched controls were enrolled. Serum/stool samples from NEC patients at acute (NEC-D) and recovery (NEC-R) phases, and controls (non-NEC) were collected. Fecal metagenomic sequencing and serum untargeted metabolomic profiling were performed. Clinical parameters were compared.ResultsThe study comprised seven NEC and seven non-NEC infants. Baseline neonatal characteristics and maternal perinatal parameters showed no significant differences between NEC-D and non-NEC except for markedly lower leukocyte counts in NEC infants. Fecal metagenomics revealed severely diminished alpha diversity in NEC-D versus both non-NEC controls and NEC-R, characterized with lower Chao1 index. NEC-D exhibited elevated Escherichia coli relative abundance alongside reduced Staphylococcus haemolyticus, Staphylococcus aureus, Staphylococcus epidermidis, and Lactobacillus paracasei. Correspondingly, KEGG functional gene analysis demonstrated impaired metabolism in NEC-D. Serum metabolomics identified significantly decreased ornithine, DL-arginine, L-threonine, leucine, and D-proline in NEC-D versus non-NEC. NEC-D also showed lower taurodeoxycholic acid, glycocholic acid, and chenodeoxycholic acid compared to NEC-R. Integrative analysis revealed a positive correlation between the metabolites D-proline and ornithine and the Lactobacillus paracasei, Staphylococcus epidermidis, and Staphylococcus aureus abundance.ConclusionNEC is characterized by gut microbiota dysbiosis with reduced diversity, altered functional gene expression, and disrupted host-microbiota metabolic crosstalk. The identified serum metabolite-microbiome correlations provide mechanistic insights into NEC pathogenesis and potential diagnostic biomarkers.